2018
DOI: 10.1002/jcb.27972
|View full text |Cite
|
Sign up to set email alerts
|

A curcumin derivative hydrazinobenzoylcurcumin suppresses stem‐like features of glioblastoma cells by targeting Ca2+/calmodulin‐dependent protein kinase II

Abstract: Glioblastoma multiforme (GBM) is the most aggressive and common type of human primary brain tumor. Glioblastoma stem‐like cells (GSCs) have been proposed to contribute to tumor initiation, progression, recurrence, and therapeutic resistance of GBM. Therefore, targeting GSCs could be a promising strategy to treat this refractory cancer. Calmodulin (CaM), a major regulator of Ca2+‐dependent signaling, controls various cellular functions via interaction with multiple target proteins. Here, we investigated the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 41 publications
4
27
0
Order By: Relevance
“…GSCs are suggested to be responsible for tumor occurrence and progression as well as chemo-and radiation-therapy resistance [2]. In line with our data, several studies have shown that different curcuminoids, such as free curcumin [55], hydrazinobenzoylcurcumin [56], and demethoxycurcumin [20], exert cytotoxic effects on GSCs. In addition, application of liposomal or phytosomal curcumin inhibits the growth of GSCs [57,58] [61].…”
Section: Discussionsupporting
confidence: 88%
“…GSCs are suggested to be responsible for tumor occurrence and progression as well as chemo-and radiation-therapy resistance [2]. In line with our data, several studies have shown that different curcuminoids, such as free curcumin [55], hydrazinobenzoylcurcumin [56], and demethoxycurcumin [20], exert cytotoxic effects on GSCs. In addition, application of liposomal or phytosomal curcumin inhibits the growth of GSCs [57,58] [61].…”
Section: Discussionsupporting
confidence: 88%
“…In line with this, curcumin derivatives exert beneficial effects on GBM due to their potential to suppress the tumorigenic features of GSCs [ 63 , 65 , 93 , 94 ]. Increasing evidence demonstrates that these synthetic compounds decrease cancer stem cell-like phenotype as well as invasive potential by targeting upstream regulators of the mTOR signaling in GSCs.…”
Section: Curcumin Suppresses Gscs’ Tumorigenicity Through Atg Indumentioning
confidence: 99%
“…It is noteworthy that curcumin recently emerges as a promising adjunct therapy against GBM owing to its potential to target GSCs [ 50 , 51 , 52 , 61 , 62 , 63 , 64 , 65 , 66 ]. This represents a sub-population of cancer cells endowed with stem-like features, such as increased self-renewal, pluripotency, and clonogenic potential [ 22 , 39 ].…”
Section: Pleiotropic Effects Of Curcumin In the Cns: From Neuropromentioning
confidence: 99%
See 1 more Smart Citation
“…CaMK-IIγ has been implicated in the signaling pathways responsible for the stemness of glioblastoma cells involving the activation of a series of transcription factors including Nanog, Sox2 and Oct4. The CaM inhibitor hydrazinobenzoylcurcumin has anti-tumor effects by inhibiting, among other processes, the migratory and the invasive capacity of glioblastoma stem cells as a result of targeting the CaMK-II/c-Ret pathway [239]. c-Ret is a tyrosine kinase receptor activated by glial-derived neurotrophic factor (reviewed in [240]).…”
Section: Cam-dependent Protein Kinasesmentioning
confidence: 99%